Avaliação da patogenicidade de isolados Mycobacterium bovis obtidos no estado de Goiás - Procopio, Victor Oliveira (2019)
The Mycobacterium bovis is the causative agent of tuberculosis in a large number of domestic and wild species. Besides the underreporting of M. bovis tuberculosis cases in humans, this bacillus causes loss of about 10 to 25% of productivity in dairy and beef cattle, and animals diagnosed with a positive tuberculin test are euthanized without financial restitution to owners. Different M. bovis isolates have been shown to present varied pathogenicity and immune response modulation. Mutations, such as those associated with single nucleotide polymorphisms (SNP), have been related to these differences. The objective of this study was to investigate wild and domestic isolates of M. bovis with a distinct clinical history in the murine model, evaluating the differences in the immune response, virulence and the probable genetic factors responsible for their virulence. The bacterial load of all organs evaluated was similar among the M. bovis isolates. However, animals infected with M. bovis isolated from Tapirus terrestris (MAt) showed early mortality (22 days) associated with pulmonary necrosis, neutrophilia and reduction of alveolar macrophages. The serum glucose levels were decreased, but the cholesterol levels increased in animals infected with MAt. After sequencing and analyzing the MAt genome, the presence of 13 SNP in virulence genes was observed and 5 of these SNP were common to other highly virulent M. bovis isolates and 4 of these were not present in MBv. One of the nsSNP (non-synonymous SNP) presented in the pknG gene (which encodes protein kinase G) promotes change in the structure of the protein's catalytic site. However, the MAt isolate showed greater growth capacity under conditions that required the action of PknG when compared to MBv and Mtb. In addition, RT-PCR from macrophages infected with MAt or MBV showed similar levels of mRNA for PknG. Cultivating macrophages infected with MAt in the presence or absence of iron, the bacterial load was greater in the supernatant than the others isolates. In conclusion, the virulence and morbidity of M. bovis isolates was associated with pulmonary neutrophilia and alveolar macrophages reduction, nsSNP in virulence genes such as pks3, pks5, mmpL4. pknG nsSNP were associated with MAt virulence that appears to modulate the macrophages to undergo necrosis due to ferropoptosis.